Berberine Encapsulated Lecithin-Chitosan Nanoparticles as Innovative Wound Healing Agent in Type II Diabetes - Dibya Sundar Panda; Hussein M. Eid; Mohammed H. Elkomy; Ahmed Khames; Randa M. Hassan; Fatma I. Abo El-Ela; Heba A. Yassin (MDPI AG, 2021)
The aim of this research is to formulate a lecithin-chitosan based nanoparticulate system loaded with berberine (BER-LC-CTS-NPs) that could be integrated into a topically applied formulation and assessed for healing wounds in a diabetic animal model. In order to formulate BER-LC-CTS-NPs, soybean lecithin, isopropyl myristate, and berberine dispersed in ethanolic solution were added into an aqueous solution of chitosan dropwise with sonication. We assessed the influence of lecithin amount, chitosan amount, and isopropyl myristate concentration on particle diameter, zeta potential, and entrapment and employed a Box-Behnken statistical design. The resulting optimized BER-LC-CTS-NPs had a mean size of 168.4 nm, a surface charge of 33.1 mV, and entrapment of 82.3%. The optimized BER-LC-CTS-NPs showed a sustained in vitro release profile. Furthermore, the potential of the optimized BER-LC-CTS-NPs integrated into a topical gel formulation for wound healing in streptozocin-induced diabetic rats was assessed. Our findings show that combining chitosan and berberine in the nanoparticles produces a synergistic effect when it comes to wound healing. The optimized nanoparticulate system works by reducing inflammation, inducing blood vessels and fibroblast proliferation, and promoting mature collagen fibers deposition. Based on the experimental results, lecithin-chitosan nanoparticles loaded with berberine have evolved as a promising strategy for accelerating wound the healing process in diabetic patients. However, the clinical merits of the developed system need to be investigated in diabetic patients.